Estudio comparativo de un sistema de freno regenerativo y regeneración con energía cinética constante en vehículos eléctricos de batería - Español, Español; Español, Español; Duran Tovar, Ivan Camilo; Español, Español (Ingeniería, 2020)
Context: The constant increase in the use of electric vehicles worldwide has motivated research to improve their autonomy compared to traditional combustion vehicles. This article presents the study of a battery charging system for electric vehicles based on the constant movement of the traction system. Method: An evaluation is carried out on a constant kinetic energy regeneration system to increase the autonomy of electric vehicles. This is achieved through the validation of a mathematical energy consumption model of a battery-based electric vehicle with a regenerative brake system, comparing the results of consumption and load states between the two energy recovery systems by means of simulations. Results: The vehicle with constant motion regeneration system consumed 42,9% more power than the one using a regenerative brake because the new system increased the total mass in the vehicle. This increase in mass means that more power must be consumed by the traction system to move the vehicle. Conclusions: The conventional regenerative brake system is more favorable with respect to the proposed regeneration system for kinetic energy, except in constant speed and zero acceleration sections.